Specificity protein 1 regulates topoisomerase IIβ expression in SH‐SY5Y cells during neuronal differentiation. Issue 10 (7th May 2014) - Guo, Hui; Cao, Cuili; Chi, Xueqian; Zhao, Junxia; Liu, Xia; Zhou, Najing; Han, Shuo; Yan, Yongxin; Wang, Yanling; Xu, Yannan; Yan, Yunli; Cui, Huixian; et al.
<x xml:space="preserve">Abstract</x> Topoisomerase IIβ (top IIβ) is a nuclear enzyme with an essential role in neural development. The regulation of top IIβ gene expression during neural differentiation is poorly understood. Functional analysis of top IIβ gene structure displayed a GC box sequence in its transcription promoter, which binds the nuclear transcription factor specificity protein 1 (Sp1). Sp1 regulates gene expression via multiple mechanisms and is essential for early embryonic development. This study seeks to determine whether Sp1 regulates top IIβ gene expression during neuronal differentiation. For this purpose, human neuroblastoma SH‐SY5Y cells were induced to neuronal differentiation in the presence of all‐trans retinoic acid (RA) for 5 days. After incubation with 10 μM RA for 3–5 days, a majority of the cells exited the cell cycle to become postmitotic neurons, characterized by the presence of longer neurite outgrowths and expression of the neuronal marker microtubule‐associated protein‐2 (MAP2). Elevated Sp1 and top IIβ mRNA and protein levels were detected and found to be positively correlated with the differentiation stage. Chromatin immunoprecipitation assay demonstrated an increased recruitment of Sp1 to the top IIβ promoter after RA treatment. Mithramycin A, a compound that interferes with Sp1 binding to GC‐rich DNA sequences, downregulated the expression of top IIβ, resulting in reduced expression of MAP2 and decreased neurite length compared with the control group. Our results indicate that Sp1 regulates top IIβ expression by binding to the GC box of the gene promoter during neuronal differentiation in SH‐SY5Y cells. © 2014 Wiley Periodicals, Inc.